Cyclic behaviour of precast reinforced concrete sandwich slender walls. (December 2020) - Rao, G. Appa; Poluraju, P.
Abstract: Experimental investigation on the performance of full scale precast RC sandwich slender walls under reversed cyclic loading is reported. Eight full scale precast 3D sandwich slender walls, with two different aspect ratios of 3.0 and 2.63, under in-plane lateral loading were tested. Four of them were designed with end stiffners, while the remaining were without stiffners. In each of four stiffened and four unstiffened walls, only two were provided with additional longitudinal reinforcement, consisting of 12 mm diameter HYSD steel rebars at 300 mm c/c spacing along on two vertical faces. All the sandwich walls were subjected to constant axial load in addition to the lateral incremental monotonic and cyclic loading using displacement control system. The performance of precast sandwich slender walls using lateral load vs. lateral displacement, pattern of cracking, displacement ductility, stiffness degradation and energy dissipation has been evaluated. The experimental results have been validated with the predicted lateral strength predicted by various codes of practice. The additional longitudinal reinforcement and end stiffeners significantly improved the lateral strength, cracking resistance, stiffness, ductility, and energy dissipation of the precast sandwich slender walls under lateral cyclic loading. The precast sandwich slender walls designed with additional longitudinal reinforcement and end stiffeners exhibited marginal improvement in the stiffness under lateral loading. The energy dissipation in the precast sandwich walls decreases in subsequent cycles of lateral displacements. The seismic base shear capacity of the precast sandwich slender walls seems to be better and comparable with the conventional RC walls.